2014
DOI: 10.1007/s11255-014-0802-2
|View full text |Cite
|
Sign up to set email alerts
|

Depression in patients with chronic kidney disease on dialysis in Saudi Arabia

Abstract: The prevalence of DD and depressive symptoms is lower in Saudi dialysis patients than in the rest of the world, largely untreated, and is associated with a distinct set of demographic, psychosocial, and physical health characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Perhaps the most surprising finding in the present study was that of a higher risk of depressive symptoms in colorectal patients of Saudi nationality. This replicates the finding reported recently of a higher risk of depression in Saudi chronic renal patients on dialysis compared to emigrant patients . Might the hardships experienced by patients emigrating from other countries to Saudi Arabia have helped them develop coping strategies for dealing with adversity, including the adversity of serious life‐theratening medical illness?…”
Section: Discussionsupporting
confidence: 86%
“…Perhaps the most surprising finding in the present study was that of a higher risk of depressive symptoms in colorectal patients of Saudi nationality. This replicates the finding reported recently of a higher risk of depression in Saudi chronic renal patients on dialysis compared to emigrant patients . Might the hardships experienced by patients emigrating from other countries to Saudi Arabia have helped them develop coping strategies for dealing with adversity, including the adversity of serious life‐theratening medical illness?…”
Section: Discussionsupporting
confidence: 86%
“…When compared to other chronic conditions, the depression prevalence among keratoconus patients in Saudi Arabia is at the middle ground between higher depression rates of sickle cell anemia (48.2%-85.9%) [22,23] and chronic pain (71%) [24] and lower depression rates of chronic kidney disease (6.8%-24.6%) [25,26] and type 2 diabetes mellitus (33.8%) [27].…”
Section: Discussionmentioning
confidence: 93%
“…[ 13 ] In one study in Saudi Arabia 24.2% of patients suffered with symptoms of major depression, however no one of the patients had been given anti-depressant medication, as patients received counseling. [ 14 ] Several studies have shown evidence of benefits of starting anti-depressant treatment. [ 10 12 15 16 17 ] Therefore, this study was designed to assess depressive symptoms in Sudanese cohort of ESRD on dialysis in an effort to deliver quality treatment of their mental health in the future.…”
Section: Introductionmentioning
confidence: 99%